115k views
0 votes
Raise the quality in parentheses to the indicated exponent, and simplify the resulting expression with positive exponents.

Raise the quality in parentheses to the indicated exponent, and simplify the resulting-example-1
User Skatch
by
5.3k points

1 Answer

5 votes

For this case we have the following expression:


(\frac {-27x ^ 0 * y ^ {- 2}} {54x ^ {- 5} * y ^ {- 4}}) ^ {- 2} =

By definition we have to:


a^0 = 1

So:


(\frac {-27y ^ {- 2}} {54x ^ {- 5} * y ^ {- 4}}) ^ {- 2} =

Simplifying:


(\frac {-y ^ {- 2}} {2x ^ {- 5} * y ^ {- 4}}) ^ {- 2} =

By definition of power properties we have to:


(a ^ n) ^ m = a ^ {n * m}

So, rewriting the expression we have:


(-1)^(-2)(-y^(-2*-2))/(2^(-2)*x^(-5*-2)*y^(-4*-2))=\\(1)/((-1)^2)*(-y^(4))/(2^(-2)x^(10)*y^(8))=

SImplifying:


+1*(y^(4-8))/(2^(-2)x^(10))=\\(y^(-4))/(2^(-2)x^(10))=\\(2^2)/(x^(10)y^(4))

Answer:


(4)/(x^(10)y^(4))

User Billy Liu
by
5.1k points